2022
DOI: 10.21203/rs.3.rs-2010335/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anatomy of the Nasal Latero-lateral Cartilage Articulation: A Micro-MRI Study in Human Specimens.

Abstract: Purpose: To study the anatomy of the latero-lateral joint (LLJ) between the upper lateral (ULC) and lower lateral (LLC) crus of the nasal cartilages, usually described as a scroll articulation. Methodology: Six nasal pyramids were taken in monobloc from fresh cadavers and imaged on micro-MRI with 0.4 mm slice thickness. Images were jointly interpreted by two head and neck radiologists and one surgeon. The junction between the ULC and LLC, the presence of ligaments and of sesamoid or accessory cartilages were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In an assessment of 8 cadaveric specimens, Haddad et al found no evidence of sesamoid cartilages utilizing a micro-MRI approach, correlating with the present study, however, they did visualize posterior accessory cartilage in 75% of subjects. 8 Further, Rohrich et al completed a cadaveric study of 10 subjects seeking to define this anatomic area, noting a fascial complex encompassing the area between the upper and lower lateral cartilage, similar to the dense fibrous tissue visualized in this study. This variability should be further investigated, introduced into nasal anatomical renderings and incorporated into educational pursuits.…”
Section: Discussionmentioning
confidence: 63%
“…In an assessment of 8 cadaveric specimens, Haddad et al found no evidence of sesamoid cartilages utilizing a micro-MRI approach, correlating with the present study, however, they did visualize posterior accessory cartilage in 75% of subjects. 8 Further, Rohrich et al completed a cadaveric study of 10 subjects seeking to define this anatomic area, noting a fascial complex encompassing the area between the upper and lower lateral cartilage, similar to the dense fibrous tissue visualized in this study. This variability should be further investigated, introduced into nasal anatomical renderings and incorporated into educational pursuits.…”
Section: Discussionmentioning
confidence: 63%